Effect of NPK fertilizer, fermented fruit peel waste, and oil palm waste compost on the soil fertility, growth and yield of okra (Abelmoschus esculentus L.) cultivated on ex-tin mining soil - Ng, Kai Li (2022)
Ex-mining soil is infertile and cannot retain water and nutrients. Therefore, amending ex-mining soil is important before crops can be planted. To date, there are limited studies in comparing the effect of fermented fruit peel waste (FFPW) and oil palm waste compost on the improvement of soil fertility, growth and yield of crops cultivated on ex-tin mining soil. The objectives of experiment are to evaluate the effect of NPK fertilizer, fermented fruit peel waste and oil palm waste compost on soil fertility of ex-tin mining soil in UTAR, Perak, as well as the growth and yield of okra cultivated on the same soil. Three blocks, each with five plants, are arranged in randomized complete block design (RCBD) subjected to four treatments: control with no fertilizer (T1), 0.1 g/kg soil NPK (15:15:15) fertilizer (T2), 25 mL/kg soil blended and diluted 1:100 fermented fruit peel waste (T3) and 50 g/kg oil palm waste compost (T4). For soil fertility parameters, T4 improved the soil fertility of the iii ex-tin mining soil by decreasing the soil pH value, increasing soil electrical conductivity, and maintaining the soil organic carbon concentration. For vegetative parameters, T4 showed significant difference (p ≤ 0.05) in increasing the leaf area to average of 615.51±176.96 cm ² , plant height (124.77±32.6 cm), stem diameter (17.02±3 mm), dry plant weight (45.36±15.35 g), dry root weight (19.91±10.41 g) number of flowers (11.67±2.79), total dry pod yield (125.24±21.35 g) and average dry pod weight (2.69±0.31 g) in comparison to other treatments. The results indicated that T4 improved the vegetative growth and yield of okra. The application of oil palm waste compost is recommended for improving soil fertility, growth and yield of crops cultivated on ex-tin mining soil, because organic matter helps the soil to hold nutrients, water and thus, help plants to uptake nutrients easily.